2021
DOI: 10.3390/su13020767
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, Social, Governance Activities and Firm Performance: Evidence from China

Abstract: Increasingly noticeable environmental and risk problems have made more and more companies and regulatory agencies realize the importance of environmental, social, and governance (ESG) activities. However, on the question that whether ESG activities have promoted or reduced firm performance, there is still no consensus. Especially for China, a representative country in emerging markets whose corporate ESG activities are still in their infancy and related systems and regulatory measures not complete, its theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(113 citation statements)
references
References 72 publications
4
61
0
3
Order By: Relevance
“…Sustainable Development Goals (SDGs) are designed to help companies meet several challenges: reputational risk management, responding to phenomena such as globalization and digitalization, proper communication with stakeholders, and meeting investor requirements for greater reporting transparency [34]. Climate change, human capital issues [6], and the increasingly visible associated risks cause more and more companies and regulators to become aware of the importance of environmental, social, and governance activities and disclosures [35]. Acting in the direction of these three dimensions, any company demonstrates what is called "corporate social responsibility".…”
Section: Background On Non-financial Disclosure and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainable Development Goals (SDGs) are designed to help companies meet several challenges: reputational risk management, responding to phenomena such as globalization and digitalization, proper communication with stakeholders, and meeting investor requirements for greater reporting transparency [34]. Climate change, human capital issues [6], and the increasingly visible associated risks cause more and more companies and regulators to become aware of the importance of environmental, social, and governance activities and disclosures [35]. Acting in the direction of these three dimensions, any company demonstrates what is called "corporate social responsibility".…”
Section: Background On Non-financial Disclosure and Hypothesis Developmentmentioning
confidence: 99%
“…Human rights scores, shareholders' scores, and management scores are the least involved. There are also studies [70][71][72][73] that show that there is a significant negative correlation between corporate ESG activities and firm performance, non-state-owned and non-environmentally sensitive companies undertake greater cost pressure on ESG activities, which in turn leads to a greater reduction in firm performance [35]. Likewise, Broadstock et al [74] find a non-linear relationship between the reporting of greenhouse gas emissions and the firm performance, noting a reluctance of companies to disclose this issue.…”
Section: Background On Non-financial Disclosure and Hypothesis Developmentmentioning
confidence: 99%
“…In addition, researchers found that CER contributes to lowering a firm's information risk [46], increases firm risk [47,48], enhances value of shareholders [49], and increases board diversity [50]. However, there also exists studies that ESG activities negatively affect firm performance [51]. For instance, Kim and Lee (2020) criticized the overinvestment behavior to maintain certain ESG performance [52].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…It should be noted that the ESG (Environmental, Social, Governance) criteria are key for investment decision-making and for encouraging more sustainable finances in pursuit of a sustainable development that integrates financial and non-financial indicators [2]. Environmental problems are well known nowadays, and companies and regulating agencies perceive the importance of environmental, social and governance activities (ESG) [3]. Furthermore, the ESG criteria are fundamental in establishing a circular economy model [4].…”
Section: Literature Reviewmentioning
confidence: 99%
“…ESG takes into account the effect the company has on the environment, both directly and indirectly; considers the company's impact on its local surroundings; and refers to the corporate governance of the company. Moreover, the pandemic caused by COVID-19, as well as financial and social world crises, have propelled ESG at different levels [2][3][4].…”
Section: Introductionmentioning
confidence: 99%